2014
DOI: 10.1051/0004-6361/201423556
|View full text |Cite
|
Sign up to set email alerts
|

The middle infrared properties of OH megamaser host galaxies

Abstract: We compiled all 119 OH maser galaxies (110 out of them are megamasers, i.e., L OH > 10 L ) published so far and cross-identified these OH masers with the Wide-Field Infrared Survey Explorer (WISE) catalog, to investigate the middle infrared (MIR) properties of OH maser galaxies. The WISE magnitude data at the 3.4, 4.6, 12 and 22 μm (W1 to W4) are collected for the OH maser sample and one control sample, which are non-detection sources. The color-color diagrams show that both OH megamaser (OHM) and non-OHM (ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Its nuclear activity is classified as H ii from optical spectroscopy (van den Broek et al 1991;Pereira-Santaella et al 2011) and there is no evidence of an AGN in this galaxy based on its mid-IR and X-ray emissions (Pereira-Santaella et al 2010b. It also host an OH megamaser (Norris et al 1986), which are associated with compact starbursts most of the times (Baan & Klöckner 2006;Zhang et al 2014). In addition, a massive outflow of neutral atomic gas is already detected in this object using optical IFS (Cazzoli et al 2014(Cazzoli et al , 2016.…”
Section: Introductionmentioning
confidence: 96%
“…Its nuclear activity is classified as H ii from optical spectroscopy (van den Broek et al 1991;Pereira-Santaella et al 2011) and there is no evidence of an AGN in this galaxy based on its mid-IR and X-ray emissions (Pereira-Santaella et al 2010b. It also host an OH megamaser (Norris et al 1986), which are associated with compact starbursts most of the times (Baan & Klöckner 2006;Zhang et al 2014). In addition, a massive outflow of neutral atomic gas is already detected in this object using optical IFS (Cazzoli et al 2014(Cazzoli et al , 2016.…”
Section: Introductionmentioning
confidence: 96%
“…Red and blue symbols are for the individual nuclei in observations with sufficient resolution to distinguish them. The data, available in NED database, were compiled from the following references: (Skrutskie et al 2006;Sanders et al 2003;Dunne et al 2000;Dunne & Eales 2001;Veilleux et al 2009;Soifer et al 1989;Brown et al 2014;Klaas et al 2001;Spinoglio et al 1995;Rangwala et al 2011;Brauher et al 2008;Förster Schreiber et al 2004;Moshir & et al 1990;Eales et al 1989;Surace et al 2000;Matsushita et al 2009;Chini et al 1986;Martín et al 2011;Rigopoulou et al 1996;Sakamoto et al 2009;Catalano et al 2014;Imanishi et al 2007;Lahuis et al 2007;Spinoglio et al 2002;Antón et al 2004;Carico et al 1992;Sargsyan et al 2011;Gorjian et al 2004;Thronson et al 1987;Leroy et al 2011;Truch et al 2008;Zhang et al 2014;Benford 1999;Weedman & Houck 2009;Brauher et al 2008) lengths are dominated by synchrotron radiation and were not considered in the fit to the thermal emission from the two nuclei.…”
Section: Observational Constraintsmentioning
confidence: 99%
“…New discoveries available in the literature (e.g., Darling & Giovanelli (2000) significantly expanded the number of known OHM galaxies. Zhang et al (2014) compiled and studied two large samples of OHM and non-OHM galaxies and found differences in their middle-infrared (MIR) properties. The main objective of our study is a comparison of radio continuum properties for these OHM and non-OHM samples.…”
Section: Introductionmentioning
confidence: 99%
“…We determined the radio properties of OMHs and compared them with the properties of a non-OHM control sample. Zhang et al (2014) compiled all 119 OH maser galaxies available in the literature (for 2014) and selected all the sources with no detection of maser emission among the updated Arecibo survey sample (Darling & Giovanelli 2002) as a control sample. We note that the selection criteria for that survey were 0.1 z 0.45, 0 • < δ < 27 • , and InfraRed Astronomical Satellite (IRAS ) detection at 60 µm.…”
Section: Introductionmentioning
confidence: 99%